Influence of Individual Differences on Computer Based Information (CBI) Usage in Banks in Sudan - Adam, Nawal  Abdalla (Gezira Journal of Economic and Social Sciences; Vol 1 No 1 (2010), 2010)
Although information technology is available in businesses to support managers to make decisions, it is important to know how individual differences among those managers affect the usage of such technology . This paper seeks to investigate the influence of individual differences (age, level of education, and years of working experience) on computer based information (CBI) usage within the framework Technology Acceptance Model (TAM ). Survey questionnaire was used to collect the research data from 120 randomly selected managers from banks in Sudan. Linear regression analysis was used to identify association between the individual differences and TAM’s basic constructs (perceived ease of use (PEOU) and perceived usefulness (PU)). The research findings indicate that the selected individual differences had a significant influence on CBI usage by managers in banks in Sudan . Regression results, also, revealed that level of education had a significant positive association with both PEOU and PU. While age and working experience had negative non significant association with both PEOU and PU. These findings have important implications on designing training programs for managers and on recruitment and selection of managers.